2018
DOI: 10.20944/preprints201807.0422.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saliva and Serum Ghrelin and Obestatin in Iron Deficiency Anemia Patients

Abstract: Ghrelin and obestatin, two antagonist peptide hormones, are purportedly involved in stimulating appetite and controlling energy balance in humans. Serum ghrelin level is also associated with iron deficiency anemia (IDA), but no study has yet been made of the obestatin level in patients with IDA, even though both hormones are a single gene product. Therefore, the purpose of this investigation is to see whether there is a link between IDA and these two hormones among other hematological parameters in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…To improve accuracy, we analyzed only data from patients with chronic liver disease, precluding data from healthy people. We noticed the sensitivity, specificity, DOR, and AUC of AFU was lower than ones of AFP (0.7352 vs. 0.7501, 0.7681 vs. 0.8208, 7.974 vs. 13.401, 0.7968 vs. 0.8451), respectively, but they are approximative, which indicates that the diagnostic value of AFU is comparable to one of AFP [17,36]. Some papers reported that the combination of AFU and AFP may improve previous diagnostic value [12,13,15,16,37].…”
Section: Discussionmentioning
confidence: 72%
“…To improve accuracy, we analyzed only data from patients with chronic liver disease, precluding data from healthy people. We noticed the sensitivity, specificity, DOR, and AUC of AFU was lower than ones of AFP (0.7352 vs. 0.7501, 0.7681 vs. 0.8208, 7.974 vs. 13.401, 0.7968 vs. 0.8451), respectively, but they are approximative, which indicates that the diagnostic value of AFU is comparable to one of AFP [17,36]. Some papers reported that the combination of AFU and AFP may improve previous diagnostic value [12,13,15,16,37].…”
Section: Discussionmentioning
confidence: 72%